Study on the Corrosion and Scale Inhibition Mechanism of the Thiourea-Modified Polyepoxysuccinic Acid (CNS-PESA). (11th May 2022) - Htet, Thin Thin; Zeng, Defang
Abstract : In this paper, thiourea-modified polyepoxysuccinic acid (CNS-PESA) was synthesized and used as a corrosion and scale inhibitor for the circulating cooling water system of the factory. Polyepoxysuccinic acid (PESA) has been widely used in industrial water treatment due to its good corrosion inhibition and scale inhibition performance. It also acts as a reliable material for dispersion of iron oxide, good biodegradation efficiency, and phosphorus-free content. The scale inhibition performance for calcium carbonate and calcium phosphate scale with corrosion inhibition performance using different inhibitor concentrations, temperatures, pH, and calcium ion concentration on scale inhibition efficiency were studied. The scanning electron microscope (SEM) analysis on the scale and corrosion of carbon steel with two methods as GB/T 18175-2000 "Measurement of inhibitors in water treatment: rotation coupon method" and electrochemical method for CNS-PESA and PESA were utilized. Compared to using CNS-PESA and PESA for calcium carbonate and calcium phosphate, the scale inhibition rates were increased by 6% and 18.7%, and the corrosion inhibition rate increased by 22.4%. The scale inhibition efficiency of CNS-PESA is best when the calcium ion concentration is less than or equal to 350 mg/L. Moreover, the thiourea-modified polyepoxysuccinic acid (CNS-PESA) was phosphorus-free corrosion and scale inhibitor and minimizes environmental pollution problems.